Establishing normal values for pediatric nighttime sleep measured by actigraphy: a systematic review and meta-analysis. Issue 4 (26th March 2018) - Galland, Barbara C; Short, Michelle A; Terrill, Philip; Rigney, Gabrielle; Haszard, Jillian J; Coussens, Scott; Foster-Owens, Mistral; Biggs, Sarah N
Abstract: Background: Despite the widespread use of actigraphy in pediatric sleep studies, there are currently no age-related normative data. Objectives: To systematically review the literature, calculate pooled mean estimates of actigraphy-derived pediatric nighttime sleep variables and to examine the magnitude of change with age. Methods: A systematic search was performed across eight databases of studies that included at least one actigraphy sleep variable from healthy children aged 0–18 years. Data suitable for meta-analysis were confined to ages 3–18 years with seven actigraphy variables analyzed using random effects meta-analysis and meta-regression performed using age as a covariate. Results: In total, 1334 articles did not meet inclusion criteria; 87 had data suitable for review and 79 were suitable for meta-analysis. Pooled mean estimates for overnight sleep duration declined from 9.68 hours (3–5 years age band) to 8.98, 8.85, 8.05, and 7.4 for age bands 6–8, 9–11, 12–14, and 15–18 years, respectively. For continuous data, the best-fit ( R 2 = 0.74) equation for hours over the 0–18 years age range was 9.02 − 1.04 × [(age/10)^2 − 0.83]. There was a significant curvilinear association between both sleep onset and offset with age ( p < .001). Sleep latency was stable at 19.4 min per night. There were significant differences among the older age groups between weekday and weekend/nonschool days (18 studies). Total sleep time in 15–18 years old was 56 min longer, and sleep onset and offset almost 1 and 2 hours later, respectively, on weekend or nonschool days. Conclusion: These normative values have potential application to assist the interpretation of actigraphy measures from nighttime recordings across the pediatric age range, and aid future research.